2016
DOI: 10.1007/s12603-015-0628-3
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of chilies, but not sweet peppers, is positively related to handgrip strength in an adult population

Abstract: This study reveals a positive correlation between frequency of chili consumption and muscle strength in adult males. Further studies are necessary in order to determine whether there is a causal relationship between chili consumption frequency and muscle strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Dietary habits was collected using a validated self-administered food frequency questionnaire that included 98 food items, with specified serving sizes described in terms of the natural portion or the standard weight and volume measurement of servings commonly consumed in general Chinese populations 32 41 42 . The FFQ included 8 frequency categories ranging from ‘almost never drink’ to ‘(≥4 servings per day’ for beverages.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary habits was collected using a validated self-administered food frequency questionnaire that included 98 food items, with specified serving sizes described in terms of the natural portion or the standard weight and volume measurement of servings commonly consumed in general Chinese populations 32 41 42 . The FFQ included 8 frequency categories ranging from ‘almost never drink’ to ‘(≥4 servings per day’ for beverages.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced handgrip strength is associated with increased disability [ 7 9 ] and mortality [ 10 , 11 ]. In addition, handgrip strength is a powerful predictor of sarcopenia [ 12 ] and frailty [ 13 ] among elderly. In this study, handgrip strength has been evaluated as an estimate of overall muscle strength [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of fatty liver was inversely associated with frequent consumption of spicy foods in a cross-sectional study including 9378 participants in China [52] . A population-based cross-sectional study found a positive correlation between frequency of chili consumption and muscle strength in adult males [53] . Healthy young men taking capsaicin analog supplementation produced higher maximal isometric force and delayed fatigue compared to those taking placebo [54] …”
Section: Spicy Food Consumption and Prevention Of Cardiometabolic Dis...mentioning
confidence: 99%